IMPLEMENTASI KOMPETENSI PROFESIONAL GURU MATEMATIKA DI ERA DIGITAL: SEBUAH STUDI KASUS - Haslina Haslina; Patma Azizah; Widiana Sari; Ade Irma (lembaga Sepercenter, 2026)
Digital era challenges trigger technostress and administrative burdens that hinder the creative teaching of mathematics teachers in schools. This study aims to explore the implementation of mathematics teachers' professional competence, its impact on student motivation, and development strategies through training, AI technology, and professional communities. Using a qualitative descriptive design, this case study examines three experienced mathematics teachers as key subjects due to their direct relevance to modern curriculum practices. The results show that professional competence integrates content mastery (PCK), technological adaptation, and work ethics. Face-to-face training is deemed more effective for knowledge retention than online formats. AI efficiently reduces administrative tasks, but the teacher's human touch in character building remains irreplaceable. In conclusion, teacher competence development heavily relies on active participation in the MGMP community and school management support. The implication is that teacher quality improvement programs must focus on direct clinical mentoring to sustainably enhance classroom instruction.